Energy levels of Ru 101 fed in the electron capture decay Rh 101m - Yuthman de Aisenberg, E.; Suarez, J. F.; Scheuer, W. (North Holland Publishing, 1966)
Fil: Yuthman de Aisenberg, E. Comisión Nacional de Energía Atómica; Argentina